2021
DOI: 10.3390/nu14010045
|View full text |Cite
|
Sign up to set email alerts
|

Association of Breastfeeding for the First Six Months of Life and Autism Spectrum Disorders: A National Multi-Center Study in China

Abstract: Previous studies have shown that exclusive breastfeeding is associated with lower odds of having autism spectrum disorders (ASD) in children, but data are lacking in Asian countries, especially China. This cross-sectional study of seven cities in China collected data from August 2016 to March 2017 from 6049 toddlers aged 16–30 months and their parents who responded to questionnaires. The breastfeeding status was collected via questionnaires based on recommendations from the World Health Organization. The stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
3
1
1
Order By: Relevance
“…A 2019 meta-analysis, involving >20 million individuals, reported that children delivered via C-section were ~30% more likely to be diagnosed with ASD than those born vaginally (36). At the same time, other research has indicated that toddlers without breastfeeding in the first 6 months of life have higher odds of developing ASD when compared to those who were exclusively breastfed (37). The results of the present study did not confirm these observations.…”
Section: Discussioncontrasting
confidence: 96%
“…A 2019 meta-analysis, involving >20 million individuals, reported that children delivered via C-section were ~30% more likely to be diagnosed with ASD than those born vaginally (36). At the same time, other research has indicated that toddlers without breastfeeding in the first 6 months of life have higher odds of developing ASD when compared to those who were exclusively breastfed (37). The results of the present study did not confirm these observations.…”
Section: Discussioncontrasting
confidence: 96%
“…In concordance with our data, there may be a link between the elevated risk of ASD and a family history of neurological and mental illnesses (26) . Hereditary or psychological variables may be responsible for this (27) . However, in this study, there was little to no correlation between having a good family history and any of the socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…However, many previous studies, have reported lower rates in children with ASD. 16,17,27 In a case -control study of Indian children from 2-6 years, George et al reported breast feeding duration under 6 months in those with ASD. 28 Another case control study of siblings from India conducted by Manohar et al found that children with ASD were sub optimally breastfed, compared to their neurotypical siblings.…”
Section: Breastfeeding Patternsmentioning
confidence: 99%